Harry Potter and the sorcerer's stone - Rowling, J. K.; GrandPrae, Mary (New York A.A. Levine Books, 1998)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Wizards and Witches.
"Year 1"--Spine.
Sequel: Harry Potter and the Chamber of Secrets.
Keywords: Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Juvenile fiction; Schools -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Juvenile fiction; England -- Fiction; Fantasy fiction -- Juvenile